Organizational culture and ambidexterity (Revista de Investigaciones Universidad del Quindío, 2023)
This article gathers the main theoretical foundations on organizational culture and ambidexterity. We will begin by delimiting the term culture, developing also its levels and main elements, as well as the concept of ambidexterity. We will review the contributions of different authors and then study the different perspectives, their forms, and the relationship between both concepts.
Keywords: ambidexterity; organizational culture; exploration